2015
DOI: 10.18632/oncotarget.2713
|View full text |Cite
|
Sign up to set email alerts
|

Molecular architecture of the ErbB2 extracellular domain homodimer

Abstract: Human epidermal growth factor receptors (HERs or ErbBs) play crucial roles in numerous cellular processes. ErbB2 is a key member of ErbB family, and its overexpression is recognized as a frequent molecular abnormality. In cancer, this overexpression correlates with aggressive disease and poor patient outcomes. Dimer-dependent phosphorylation is a key event for the signal transduction of ErbBs. However, the molecular mechanism of the dimerization of ErbB2 remains elusive. In the present work, we report the homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…Recently, we have determined the crystal structure of ErbB2 in complex with H2-18. Our crystallographic analysis confirmed that the epitope of H2-18 is in domain I of ErbB2 [23]. Competitive binding assays also showed that H2-18 did not compete with either trastuzumab or pertuzumab for binding to ErbB2 (Supplementary Figure S1).…”
Section: Resultssupporting
confidence: 71%
“…Recently, we have determined the crystal structure of ErbB2 in complex with H2-18. Our crystallographic analysis confirmed that the epitope of H2-18 is in domain I of ErbB2 [23]. Competitive binding assays also showed that H2-18 did not compete with either trastuzumab or pertuzumab for binding to ErbB2 (Supplementary Figure S1).…”
Section: Resultssupporting
confidence: 71%
“…Another potential explanation for negative cooperativity could be steric hindrance for the second HER2 molecule. Due to the high flexibility of the domain IV of HER2, a total of 55 residues on the C-terminus could not be resolved, which is also the case for other structures of HER2 (Franklin et al, 2004;Hu et al, 2015). However, the HER2 molecule of the trastuzumab Fab-HER2 complex structure (Cho et al, 2003), where the Fab fragment binds at the lower end of domain IV, shows more electron density in domain IV and therefore misses only 24 residues on the C-terminal part.…”
Section: Discussionmentioning
confidence: 99%
“…Reflecting our previous in vitro computational model, we account for binding of matrix-bound ligands to VEGFR2 (previously demonstrated [18, 19]) and VEGFR1 (assumed to occur). We assume that endothelial basement membrane-bound growth factor within 25nm of the cell surface is accessible to cell surface receptors, based on the length of the extracellular domain of the related RTKs ErbB2 and ErbB3 (11.3–16.4nm) [7375], and assuming some flexibility in cell position and shape. We calculated the resulting fraction of EBM accessible to cell surface receptors (S7 Table), and scaled the corresponding reaction on-rates (Table 2, see S1 Equations).…”
Section: Methodsmentioning
confidence: 99%